Effect of micro-textured tools on machining of Ti–6Al–4V alloy: An experimental and numerical approach. (January 2016) - Arulkirubakaran, D.; Senthilkumar, V.; Kumawat, Vijay
Abstract: In this work, an attempt is made to reduce the detrimental effects that occurred during machining of Ti–6Al–4V by employing surface textures on the rake faces of the cutting tools. Numerical simulation of machining of Ti–6Al–4V alloy with surface textured tools was employed, taking the work piece as elasto-plastic material and the tool as rigid body. Deform 3D software with updated Lagrangian formulation was used for numerical simulation of machining process. Coupled thermo-mechanical analysis was carried out using Johnson-cook material model to predict the temperature distribution, machining forces, tool wear and chip morphology during machining. Turning experiments on Ti–6Al–4V alloy were carried out using surface textured tungsten carbide tools with micro-scaled grooves in preferred orientation such as, parallel, perpendicular and cross pattern to that of chip flow. A mixture of molybdenum disulfide with SAE 40 oil (80:20) was used as semi-solid lubricant during machining process. Temperature distribution at tool–chip interface was measured using an infrared thermal imager camera. Feed, thrust and cutting forces were measured by a three component-dynamometer. Tool wear and chip morphology were captured and analyzed using optical microscopic images. Experimental results such as cutting temperature, machining forces and chip morphology were used for validating numerical simulation results. Cutting tools with surface textures produced in a direction perpendicular to that of chip flow exhibit a larger reduction in cutting force, temperature generation and reduced tool wear. Graphical abstract: Highlights: Surface texturing was performed on the rake face of the cutting tool in preferred orientation by wire-EDM process. Tool-chip contact length, cutting temperature and cutting forces were found to be less in textured tools. Less coefficient of friction and less tool wear were observed in all types of textured tools. Textured tools produced curled type of saw-toothed chips with reduced curl-diameter. Machinability of Ti-6Al-4V alloy exhibits better performance in textured tools especially in perpendicular textured tool.